Microbial Hazards in Irrigation Water: Standards, Norms, and Testing to Manage Use of Water in Fresh Produce Primary Production. Issue 4 (10th April 2015) - Uyttendaele, Mieke; Jaykus, Lee‐Ann; Amoah, Philip; Chiodini, Alessandro; Cunliffe, David; Jacxsens, Liesbeth; Holvoet, Kevin; Korsten, Lise; Lau, Mathew; McClure, Peter; Medema, Gertjan; Sampers, Imca; et al.
Abstract Accessibility to abundant sources of high‐quality water is integral to the production of safe and wholesome fresh produce. However, access to safe water is becoming increasingly difficult in many parts of the world, and this can lead to the production of fresh produce contaminated with pathogenic microorganisms, resulting in increased risk of human disease. Water, an important raw material in the fresh produce chain, is used in considerable amounts in many operations, including irrigation and application of pesticides and fertilizers, but also as a transport medium and for cooling and washing in postharvest practices. In several reported outbreaks related to uncooked fruit and vegetable products, water has been identified as a likely source of the outbreak. The present study, initiated by the ILSI Europe Emerging Microbiological Issues Task Force in collaboration with 8 other ILSI branches and support of WHO/FAO, was undertaken to review the status of, and provide suggestions for, consideration by different stakeholders on water and sanitation and its impact on food safety and public health. A limited number of guidelines and regulations on water quality for agricultural production are available, and many of them are still heavily based on microbial standards and (debated) parameters such as fecal coliforms. Data gaps have been identified with regard to baseline studies of microbial pathogens in water sources in many regions, the need for agreement on methods and microbial parameters to be used in assessing water quality, the fate of pathogens in water, and their transfer and persistence on irrigated/processed produce.